THE INFLUENCE OF ORGANIZATIONAL CULTURE, ORGANIZATIONAL COMMITMENT AND MOTIVATION ON PERFORMANCE EMPLOYEE AT PT. KPP - Rizkah, Rizkah; Chaerudin, Chaerudin (Dinasti Publisher, 2021)
This study aims to analyze the influence of organizational culture, organizational commitment and motivation on performance employee at PT. KPP, with a population 77 people are all employees of PT. KPP. The sampling method used is non-probability sampling and the form of the sampling technique is the saturated sampling technique. Multiple linear regressions as the data analysis technique used. There is a significant influence between organizational culture and motivation but organizational commitment does not partially significantly affect the performance of employees of PT. KPP, finding the results of organizational culture, organizational commitment and motivation simultaneously have to effect on the performance of employees PT. KPP